ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESADARAN MEMILIKI NOMOR POKOK WAJIB PAJAK (NPWP) PADA PEMILIK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN KAMPAR - Zulfi Arsad; Yessi Mutia Basri; Azhari sofian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to know the influence of needs, convenience, sanctions, and the perception of the consciousness have a Taxpayer Identification Number (TIN) In The District Kampar. This study used a simple technique accidental sampling with a sample of 100 people who have been determined based on those results slovin formula. Data collection techniques in this study is a questionnaire , the data is processed using Logistic Regression with SPSS version 20. The results showed that the variable needs to have a TIN, convenience variables have a TIN, and tax penalties variables affect the consciousness have a Taxpayer Identification Number (TIN) while the variable perception of taxation does not affect the consciousness have a Taxpayer Identification Number (TIN). The coefficient of determination (R2) value of R Square of 0.446 indicates that awareness of the WP in Kampar regency have a TIN is affected by the variable needs, ease, perception WP and tax penalties amounting to 44.6%. While about 55.4% influenced by other variablesKeyword : Awareness have a TIN, needs to have a TIN, the convenience of having a TIN, sanctions taxation, taxation perception.